Neutrophil-to-Lymphocyte Ratio Predicts Outcomes in Patients Implanted with Left Ventricular Assist Devices. Issue 6 (November 2015) - Yost, Gardner L.; Joseph, Christine R.; Tatooles, Antone J.; Bhat, Geetha
Abstract : The neutrophil-to-lymphocyte ratio (NLR) has been used to predict mortality in a wide range of cardiovascular diseases including acute decompensated heart failure and non-ST-elevation myocardial infarction. We investigated the prognostic utility of the NLR in patients with advanced heart failure who received left ventricular assist devices (LVADs). Two hundred seventy-three patients implanted with LVADs at our institution were divided into tertiles based on their NLR and were retrospectively analyzed. Outcomes, including survival and right ventricular (RV) failure, were compared between tertiles. The NLR was found to be an independent predictor of postoperative mortality (odds ratio [OR] = 1.159, confidence interval [CI] = 1.022–1.314, p = 0.021) and of postoperative RV failure (OR = 1.117, CI = 1.039–1.201, p = 0.003). In addition, patients in the highest NLR tertile were found to have significantly increased postoperative length of stay (tertile 1 = 20.6 ± 10.7 days, tertile 2 = 24.2 ± 20.7 days, and tertile 3 = 28.8 ± 18.6 days, p = 0.001). In conclusion, the NLR is a simple and practical method for predicting adverse outcomes including all-cause mortality and RV failure after LVAD implantation.